2020
DOI: 10.3389/fphar.2020.00498
|View full text |Cite
|
Sign up to set email alerts
|

Specific Interaction With Human Serum Albumin Reduces Ginsenoside Cytotoxicity in Human Umbilical Vein Endothelial Cells

Abstract: Human serum albumin (HSA) is an important component of plasma, which has the functions of maintaining colloid osmotic pressure and capillary membrane stability, promoting blood circulation, and anti-oxidation. Three-dimensional structure of HSA determines its ability to bind and transport hormones and other substances. In this study we examined the interactions between HSA and ginsenoside Rg3, Rg5, Rk1, Rh2, and Rh4, which are the main cytotoxic ginsenosides extracted from red ginseng. Heat transfer generated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…It has been reported that human serum albumin (HSA) can interact with (20S)G-Rh2, (20S)G-Rg3, G-Rk1, G-Rg5, G-Rh4, and CK because of the sequence homology between HSA and BSA. Additionally, the binding sites are located in different domains of HSA [ 39 , 40 ]. Taken together, we can summarize some characteristics of ginsenosides.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that human serum albumin (HSA) can interact with (20S)G-Rh2, (20S)G-Rg3, G-Rk1, G-Rg5, G-Rh4, and CK because of the sequence homology between HSA and BSA. Additionally, the binding sites are located in different domains of HSA [ 39 , 40 ]. Taken together, we can summarize some characteristics of ginsenosides.…”
Section: Discussionmentioning
confidence: 99%
“…Herein, we showed that G-Rk1 and G-Rg5 both have cytotoxic effects on MHCC-97H cells by inducing apoptosis. In our previous study, we determined the cell viability of human umbilical vein endothelial cells (HUVEC) in treatment with G-Rk1 and G-Rg5 by MTT, with an IC 50 of 12.272 μg/mL and 10.182 μg/mL, respectively [ 39 ]. Combined with the results of this study, it demonstrated that the cytotoxic effect of G-Rk1 and G-Rg5 on normal tissue cells is less than that on MHCC-97H cells.…”
Section: Discussionmentioning
confidence: 99%
“…Albumin and globulins are the two most abundant proteins in human blood plasma and can be easily and cost-effectively measured. As the major serum protein, albumin plays an vital role in carrying out antioxidant activities, maintaining colloidal osmotic pressure, binding and transporting hormones, cations and fatty acids, as well as in maintaining capillary membrane stability ( 41 , 42 ). Similarly, the albumin level either reflects the body nutritional status or represents the systemic inflammation ( 43 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ginsenoside Rg3 is the original ginsenoside compound and is one of the active components of ginseng stems, leaves, and roots (Lee et al, 2020; Nakhjavani et al, 2020). Rg3 can produce a variety of pharmacological effects, such as anti‐oxidation, anticancer, anti‐inflammation, and antiaging (Li et al, 2020; Min et al, 2006; Shi et al, 2020; Zhang et al, 2018, 2020). In addition, Rg3 can induce memory impairment, neurotoxicity, depression‐like behavior defects, and other potential effects (Aalinkeel et al, 2018; Kang et al, 2017; Li et al, 2020).…”
Section: Introductionmentioning
confidence: 99%